2016
DOI: 10.9734/bbj/2016/25955
|View full text |Cite
|
Sign up to set email alerts
|

Production and Application of Agar-based Slow-release Fertilizers, in the Bioremediation of Petroleum Hydrocarbon-impacted Soil

Abstract: Aims:The study was carried out to determine the potentials of novel slow-release fertilizers (SRF) in the bioremediation of petroleum hydrocarbon-impacted soil, in order to determine their potentials in the bioremediation of petroleum-impacted sites and as well evaluate the effect of nutrient concentration on the rate of bioremediation. Study Design: A marine biopolymer (agar agar) was used as a coating for soluble NPK fertilizer in slow-release formulations (capsular and granular form).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Poultry and soybean waste are organic in nature and organic manures are believed to be slow release in nature and may be affected by the early stage nutrient deficiency phenomena as stated by Sampson et al, (2016). It follows that at the early state the nutrients are released at rates that do not support much microbial growth necessary for high microbial proliferation, compared to the direct inorganic fertilizer application.…”
Section: Bacterial Population Dynamics In Soil During Bioremediationmentioning
confidence: 99%
“…Poultry and soybean waste are organic in nature and organic manures are believed to be slow release in nature and may be affected by the early stage nutrient deficiency phenomena as stated by Sampson et al, (2016). It follows that at the early state the nutrients are released at rates that do not support much microbial growth necessary for high microbial proliferation, compared to the direct inorganic fertilizer application.…”
Section: Bacterial Population Dynamics In Soil During Bioremediationmentioning
confidence: 99%
“…Recently, super-absorbent hydrogels and synthetic hydrogels have shown significant promise in the market, whereas natural hydrogels have drawn more attention because of their availability, environmental safety, and cost-effectiveness [27,28]. Among these natural hydrogels, chitosan- [29], starch- [3], cellulose- [30], gelatin- [31], and algae-based hydrogels including alginate [32], carrageenan [33], agar [34] and agarose [35] have attracted great research interest towards slow-release fertilizer applications.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have discovered that agar can be employed as a matrix for the prolonged release of pharmaceuticals [48][49][50]. The study conducted by Sampson et al [34] explored the use of agar as a coating material for soluble NPK fertilizer in both capsular and granular slow-release formulations. In contrast, agar hydrogel is utilized in a double network hydrogel system with starch for herbicide control release, and it has been shown that agar helps promote soil health [51].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most critical steps are choosing the right carrier for a new bioinoculant formulation, its combination with the microorganisms in the basal medium as well as the selection of a highly effective strain (Bargaz et al, 2018). Bioinoculants for seeds pre-inoculation formulated on carriers such as sodiumalginate (SA), agar (A) and polyvinylpyrrolidone (PVP) are proven to have a great potential, mostly due to their ability to gradually release fertiliser in the soil during the time (Sampson et al, 2016;Bargaz et al, 2018;Ramli, 2019). Furthermore, these carriers do not interfere with the survival of rhizobial cells in the biofertilizer.…”
Section: Introductionmentioning
confidence: 99%